2012
DOI: 10.1364/oe.20.018303
|View full text |Cite
|
Sign up to set email alerts
|

Digital Fresnel holography beyond the Shannon limits

Abstract: This paper presents a detailed analysis of the influence of the pixel dimension in digitally-recorded holograms. The investigation is based on both theoretical and experimental viewpoints for recordings beyond the Shannon limits. After discussing the pixel paradox, the sinc amplitude modulation is experimentally demonstration. The experimental analysis is well correlated to the theoretical basics; in addition, the filling factor of the sensor can be estimated. The analysis of the phase changes of the object sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In order to increase W to 3 mm for M = 8, we need to increase the coherence length to about 1 mm, which is equal to ∆λ = 0.32 nm at λ = 600 nm. We should note that the distribution of k m a, similar to the one given in figure 7, can potentially be recorded with aliasing without a grating [26], but the visibility of the fringes will be reduced because of the averaging of the image introduced by the finite size of the pixels [50,51]. The larger the fill factor of the sensor (the ratio of pixel size to pixel spacing), the faster the visibility decreases with increasing carrier frequency.…”
Section: Angular Multiplexing Using Additional Element In Reference Armmentioning
confidence: 87%
“…In order to increase W to 3 mm for M = 8, we need to increase the coherence length to about 1 mm, which is equal to ∆λ = 0.32 nm at λ = 600 nm. We should note that the distribution of k m a, similar to the one given in figure 7, can potentially be recorded with aliasing without a grating [26], but the visibility of the fringes will be reduced because of the averaging of the image introduced by the finite size of the pixels [50,51]. The larger the fill factor of the sensor (the ratio of pixel size to pixel spacing), the faster the visibility decreases with increasing carrier frequency.…”
Section: Angular Multiplexing Using Additional Element In Reference Armmentioning
confidence: 87%
“…(39). Furthermore, the finite dimensions of the pixels and the coherence here are not taken into account [35].…”
Section: The Case Of An Anamorphic Optical Systemmentioning
confidence: 99%
“…The sampling conditions have been well studied in the DH systems [15][16][17][18][19][20][21]. In brief, for a band-limited input optical signal with the size L and spatial frequency bandwidth W, the information density or its space-bandwidth product (SBP) can be defined as SBP = LW, where only one dimension is considered for simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that these non-overlapping intervals could be significantly extended by applying the subtraction digital holography method [17,18]. The influence of the pixel dimension for hologram recordings beyond the Shannon limits was also investigated [19]. The space bandwidth available for recording an object wave in an off-axis configuration was extended by intentionally setting the aliasing to the recorded hologram [20].…”
Section: Introductionmentioning
confidence: 99%